Value of brain computed tomographic angiography to predict post thrombectomy final infarct size and clinical outcome in acute ischemic stroke - Apirakkan, Mungkorn; Vuthiwong, Withawat; Kobkitsuksakul, Chai; Keandoungchun, Jesada; Chanthanaphak, Ekachat (Asian Journal of Neurosurgery, 2019)
Aims: This study aims to analyze the predictor in preoperative brain computed tomographic angiography (CTA) for final infarct and outcome in postendovascular thrombectomy patient. Subjects and Methods: 52 patients were retrospectively reviewed. The Alberta Stroke Program Early Computed Tomography Score (ASPECTS) comparison between preoperative noncontrast computed tomography (NCCT) and 24-h NCCT as well as preoperative CTA source image (CTA-SI) and 24-h NCCT were performed. Factors associated with increased ASPECTS and clinical outcome were evaluated. Results: Preoperative NCCT ASPECTS = 24-h NCCT in 23%. Whereas, 46% showed preoperative CTA-SI ASPECTS = 24-h NCCT. Moreover, 40.4% showed 24-h NCCT ASPECTS > preoperative CTA-SI (increased ASPECTS). The two significant factors associated with increased ASPECTS are thrombolysis in cerebral infarct score 2b/3 (P = 0.02) and good collateral status (P = 0.02). Finally, good clinical outcome was associated with age <60 (P = 0.04), preoperative CTA-SI ASPECTS >5 (P = 0.01), good collaterals status (P = 0.02), and increased ASPECTS (P = 0.05). Conclusions: Preoperative brain CTA provided the necessary factors that are associated with good clinical outcomes, which are CTA-SI ASPECTS > 5, good collateral status, and increased ASPECTS.
Keywords: Computed tomographic angiography source image Alberta Stroke Program Early Computed Tomography Score; final infarct volume; increase Alberta Stroke Program Early Computed Tomography Score; stroke outcome